1989
DOI: 10.1159/000185580
|View full text |Cite
|
Sign up to set email alerts
|

Furosemide and Dopamine in Malarial Acute Renal Failure

Abstract: The effects of furosemide and furosemide with dopamine on renal function were studied in 23 patients with acute renal failure due to falciparum malaria whose serum creatinine ranged from 230 to 947 μmol/l. Furosemide given intravenously at the dosage of 200 mg 6 hourly for a period of 4 days did not alter the clinical course of renal failure. Intravenous administration of furosemide (200 mg 6 hourly) with dopamine (1 μg/kg/min) for 4 days increased creatinine clearance and arrested the progress of renal failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(10 citation statements)
references
References 20 publications
(26 reference statements)
1
9
0
Order By: Relevance
“…Of these, six were excluded; the remaining 15 trials [8, 30,31,32,33,34,35,36,37,38,39,40,41,42,43] were included in this meta-analysis. Articles were excluded for the following reasons: dopamine was combined with another agent [44,45,46], outcome variables not recorded [47], and pediatric patients were studied [48,49]. Overall, 970 patients were enrolled in the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, six were excluded; the remaining 15 trials [8, 30,31,32,33,34,35,36,37,38,39,40,41,42,43] were included in this meta-analysis. Articles were excluded for the following reasons: dopamine was combined with another agent [44,45,46], outcome variables not recorded [47], and pediatric patients were studied [48,49]. Overall, 970 patients were enrolled in the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…In this study as well as the previous study on malaria, there is only a single infectious cause without complications. [1] It is clean acute renal failure where only hemodynamic changes play the role. Like in malaria, this regime of treatment does not benefit leptospirosis patients with severe renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…Increased urine flow and the rapid improvement of renal function are observed. In a previous study of patients with falciparum malaria, dopamine and furosemide attenuated the progression of mild renal failure [1] but failed to prevent the progression of moderate and severe renal failure. The experience with tropical disease conflicts with the concept that dopamine and its combination with furosemide offer no benefit in the early stage of acute renal failure.…”
Section: Introductionmentioning
confidence: 88%
“…There is an abundance of clinical studies that have evaluated loop diuretics for the management of AKI [67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85] (table 4). Regrettably, the majority of these studies have shortcomings and also have not shown the use of loop diuretics leads to improved clinical outcomes.…”
Section: Diuretic Therapy In Akimentioning
confidence: 99%